Prokaryotic homeostasis – a solution to thrive and survive - Barańska, Sylwia; Boss, Lidia; Gąsior, Filip; Glinkowska, Monika; Kędzierska, Barbara; Maciąg-Dorszyńska, Monika; Nowicki, Dariusz; Potrykus, Katarzyna; Szalewska-Pałasz, Agnieszka (Frontiers in Molecular Biosciences, 2025)
Bacteria have been generally greatly overlooked in the aspect of intra- and extra-cellular homeostasis, and yet, since they have evolved intricate processes and mechanisms allowing them not only to stay alive but also thrive in favorable and unfavorable environments alike, they should be considered as a close-to-ideal example of single-cell homeostasis. The bacterial responses aimed at maintaining homeostasis, while adjusting and reacting smoothly and swiftly to any changes inside and outside the cell, involve complex transcriptional networks regulated by second messengers and DNA topology, but also influenced by the presence of prophages and toxin-antitoxin systems. Their adjustment to nutrient availability also involves homeostasis in energy-related processes, such as central carbon metabolism, and crucial ion acquisition, e.g., iron. The genome stability, which is indispensable to maintain a given organisms’ functions, is achieved by control of DNA replication and repair. Furthermore, bacteria can form multicellular structures (biofilms), where homeostasis is achieved at several different levels and provides bacteria with higher chances of survival and colonization of new niches and locations. Precise correlation between the above-mentioned cellular processes makes bacteria highly intriguing objects of studies. Homeostasis is the most important basis of their life-style flexibility, thus understanding of these processes is indispensable for both: the basic and applied sciences. For example, understanding how chromosomal architecture and DNA topology coordinate global gene expression is essential for optimizing strain engineering and synthetic biology applications. Moreover, bacterial homeostasis regulatory processes can be employed as targets for antibacterial agents and prospective therapies.